Blockchain Technology In The Perspective Of Public Accounting In Indonesia - Koerniawan, Iwan; Wibowo, Agus (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2023)
Examine the supporting and inhibiting factors for the readiness to adopt blockchain technology and their implications for the sustainability of the public accounting profession. This research design is quantitative, by determining the population of all public accountants in KAPs throughout Indonesia, as many as 6,034 people. Probability sampling design, with reference to the sample size if the population is > 4,000 then between 5-10% can be considered representative. Based on this, the sample in this study was set at 7.2% (433 respondents). The main data source is primary data, through a questionnaire instrument with a Likert scale that strongly disagrees to strongly agrees. The independent variables consist of supporting and inhibiting factors, mediating variables on the readiness to adopt blockchain technology, and the dependent variable on the sustainability of the public accounting profession. Testing was carried out using path analysis, which was first tested for the validity of Kaiser Meyer Olkin (KMO), and the reliability of Alpha Cronbach. Conclusion: Supporting and inhibiting factors partially have a positive and significant effect on the readiness to adopt blockchain technology as well as on the sustainability of the public accounting profession. The readiness for blockchain adoption has no effect on the sustainability of the public accounting profession, so it is not a reinforcing variable.